DESCRIPTION OF NUTRITIONAL STATUS IN STUDENTS OF PUBLIC HEALTH STUDY PROGRAM, FACULTY OF MEDICINE AND HEALTH SCIENCES UIN ALAUDDIN MAKASSAR - Syamsul Alam; Sukfitrianty; Nildawati; Syarfaini (Andragogi Kesehatan, 2024)
Currently, Indonesia faces a double nutrition problem, namely the problem of undernutrition and more nutrition, especially in adolescents. Nutritional deficiencies during adolescence will have an impact until adulthood which not only affects cognitive aspects but also becomes a major risk factor for infectious and sexual diseases. This study aims to determine the picture of nutritional status in students, especially BMI status, energy intake, carbohydrates, proteins and fats. This study used a descriptive study design, with a sample of 102 students in the Public Health Study Program of UIN Alauddin Makassar. The results showed that from 102 respondents, there were 25 respondents (24.5%) who belonged to the category of undernutrition, 62 respondents (60.8%) who belonged to the normal category, and 15 respondents (14.7%) who belonged to the category of overnutrition. In adolescents, efforts are needed to maintain nutritional status so that it is always in optimal condition, namely by referring to balanced nutrition, where eating food according to the portion of each individual and avoiding imbalances between nutrients.